PENGARUH KEPEMIMPINAN PENGELOLA, IKLIM KOMUNIKASI DAN MOTIVASI KERJA TERHADAP KINERJA TUTOR PADA PKBM KARANG PUTIH KELURAHAN BATU GADANG KECAMATAN LUBUK KILANGAN KOTA PADANG - Azni, Fithri; Mukhaiyar, Mukhaiyar; Rusdinal, Rusdinal (English Department FBS UNP, 2011)
The tutor performance at PKBM was a critical success factors of an organization. Based on initial survey on the performance of tutors PKBM Karang Putih Kelurahan Batu Gadang Kecamatan Lubuk Kilangan Kota Padang was found that the performance is still low. The symptoms are thought to relate closely with the management leadership, communication climate, work motivation. This study aims to determine empirically how much influence the management leadership, the communication climate, the work motivation to the performance of tutors, the the management leadership through work motivation to the performance of tutors, the communication climate through work motivation to the performance of tutors.The performance of tutorâ€™s at PKBM Karang Putih Kelurahan Batu Gadang Kecamatan Lubuk Kilangan Kota Padang can be increased byÂ improving the leadership of organizer, communications climate and work motivation.